European Stroke Organisation (ESO) Guidelines for the Management of Temperature in Patients with Acute Ischemic Stroke. Issue 6 (August 2015) - Ntaios, George; Dziedzic, Tomasz; Michel, Patrik; Papavasileiou, Vasileios; Petersson, Jesper; Staykov, Dimitre; Thomas, Brenda; Steiner, Thorsten; ,
Background: Hyperthermia is a frequent complication in patients with acute ischemic stroke. On the other hand, therapeutically induced hypothermia has shown promising potential in animal models of focal cerebral ischemia. This Guideline Document presents the European Stroke Organisation guidelines for the management of temperature in patients with acute ischemic stroke. Methods: A multidisciplinary group identified related questions and developed its recommendations based on evidence from randomized controlled trials elaborating the Grading of Recommendations Assessment, Development, and Evaluation approach. This Guideline Document was reviewed within the European Stroke Organisation and externally and was approved by the European Stroke Organisation Guidelines Committee and the European Stroke Organisation Executive Committee. Results: We found low-quality evidence, and therefore, we cannot make any recommendation for treating hyperthermia as a means to improve functional outcome and/or survival in patients with acute ischemic stroke and hyperthermia; moderate evidence to suggest against routine prevention of hyperthermia with antipyretics as a means to improve functional outcome and/or survival in patients with acute ischemic stroke and normothermia; very low-quality evidence to suggest against routine induction of hypothermia as a means to improve functional outcome and/or survival in patients with acute ischemic stroke. Conclusions: The currently available data about the management of temperature in patients with acute ischemic stroke are limited, and the strengths of the recommendations are therefore weak. We call for new randomized controlled trials as well as recruitment of eligible patients to ongoing randomized controlled trials to allow for better-informed recommendations in the future.